Work-Life Balance, Kepuasan Kerja, dan Kinerja Di Antara Karyawan Milenial dan Gen Z: Tinjauan Sistematis: Work-Life Balance, Job Satisfaction and Performance Among Millennial and Gen Z Employees: A Systematic Review - Evi C Waworuntu; Sandra J. R. Kainde; Deske W Mandagi (Society, 2022)
Although the impact of work-life balance and job satisfaction on employee performance has been extensively studied, there still lacks a comprehensive understanding of the interplay among these variables among millennials and generation Z (gen Z) employees. This present inquiry, therefore, aims to systematically analyze how work-life balance and job satisfaction affect millennials’ and gen Z’s performance. Following a systematic literature review approach, relevant studies published in 2018-2022 were derived from two main academic databases (Google scholar and Research gate). Thirty-five peer-reviewed articles were then carefully selected and analyzed. The result shows that (1) work-life balance and job satisfaction positively affect millennial’s and gen Z’s performance; (2) gen Z are more idealists in thriving for work and growth (3) millennials and gen Z put a value on the supportive work environment, supportive supervisor, and career opportunity for job satisfaction (4) millennial and gen Z put a value on flexibility of work hours, annual leave and work from home for work-life balance.